When lights tell stories: The untold economic pattern of Java island - Avi Aviliani; Matthew Kartawinata; Jonathan Ersten Herawan; Firman Parningotan; Angelina Komala (Jurnal Ekonomi Indonesia, 2026)
Purpose — This study evaluates the role of Nighttime Lights (NTL) as a complementary indicator of regional economic and socio-economic development across Java Island. Method — Using VIIRS NTL data for 2016–2023, the study compares radiance patterns with GRDP per capita, Human Development Index (HDI), population density, and road infrastructure across six provinces. The analysis combines spatial visualization, growth comparison, and correlation analysis. Findings — Results show that NTL effectively captures the spatial concentration and dynamics of economic activity, but its relationship with development indicators varies across regions. Strong alignment appears in highly urbanized provinces such as DKI Jakarta, while weaker or divergent patterns are observed in regions with service-based or dispersed economies.Implications — NTL can support policy analysis by revealing spatial disparities and real-time economic dynamics, but it should be used cautiously as a complementary rather than standalone indicator. Originality — This study provides a subnational, multidimensional assessment of NTL in Java, highlighting its context-dependent reliability as a proxy for development.